Manufactures Building construction, Washington Restaurant, Cascades, and Geyser Basin, Alaska-Yukon-Pacific Exposition, Seattle, Washington, Spring 1908 - Nowell, Frank H., 1864-1950 (1908)
On verso of photograph: Manufactures bldg. PH Coll 727.445 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number